Differential prognostic value of MYC immunohistochemistry in subtypes of papillary renal cell carcinoma. Issue 1 (December 2017) - Bellut, Julia; Bertz, Simone; Nolte, Elke; Stöhr, Christine; Polifka, Iris; Lieb, Verena; Herrmann, Edwin; Jung, Rudolf; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; Wach, Sven
Abstract The histomorphological subtyping of papillary renal cell carcinomas (pRCCs) has improved the predictions of patients' long-term survival. Based on our previous results, we hypothesized that the MYC proto-oncogene would show differential expression in pRCC subtypes. Using a multi-institutional cohort of 204 pRCC patients we assessed the additional value of the immunohistochemical markers MYC, MINA53, and Ki67 in predicting patient's long-term survival. The clinical endpoints were overall survival (OS) and cancer-specific survival (CSS). Nomograms were constructed to predict each patient's risk of death (OS). The incorporation of the MYC staining patterns allowed the stratification of pRCC type 1 patients into better and worse prognostic groups. None of the patients with pRCC type 1 tumors and favorable MYC staining patterns died from tumor-related causes. This prognostic value was independent of the patient's age at surgery, the pathological tumor stage and presence of lymph node invasion. we could show that the immunohistochemical assessment of MYC and the histomorphological subtyping of pRCC stratifies pRCC type 1 tumors with regard to OS and CSS. The determination of the histomorphologic pRCC subtype in combination with the MYC immunohistochemical staining patterns allows a more accurate prediction of patients' individual risk of death.